2017
DOI: 10.1163/18773109-00901006
|View full text |Cite
|
Sign up to set email alerts
|

“I think” in political speech

Abstract: Simon-Vandenbergen (2000: 61) concluded her study of I think in political discourse by noting the importance of further study of its prosodic realisation. Consequently, I investigate the prosodic realisations of I think in political debates. At the same time, I examine the lexico-grammatical form of the construction, and its surrounding co-text. My exploration confirmed that I think is frequent in political speech, and revealed that it projected four types of meanings. Three of the meanings occurred irrespect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A number of studies have been made to examine the use of this type of modality in spoken and written discourse, especially political discourse (see, e.g., Baumgarten & House, 2010;Boicu, 2008;Fetzer, 2011Fetzer, , 2014Fraser, 2010;Hernández-Guerra, 2016;Lillian, 2008;López, 2012;Milkovich & Sitarica, 2017;O'Grady, 2017;Simon-Vandenbergen, 1996, 1997, 2000Vukovic, 2014ab). Some of these studies have focused on very specific features such as the form, function and distribution of the 'parenthetical' construction (Urmson, 1952) I think (Fetzer, 2011;O'Grady, 2017;Simon-Vandenbergen, 2000), and I think, I mean and I believe (Fetzer, 2014). These studies revealed the frequent use of I think in political discourse.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been made to examine the use of this type of modality in spoken and written discourse, especially political discourse (see, e.g., Baumgarten & House, 2010;Boicu, 2008;Fetzer, 2011Fetzer, , 2014Fraser, 2010;Hernández-Guerra, 2016;Lillian, 2008;López, 2012;Milkovich & Sitarica, 2017;O'Grady, 2017;Simon-Vandenbergen, 1996, 1997, 2000Vukovic, 2014ab). Some of these studies have focused on very specific features such as the form, function and distribution of the 'parenthetical' construction (Urmson, 1952) I think (Fetzer, 2011;O'Grady, 2017;Simon-Vandenbergen, 2000), and I think, I mean and I believe (Fetzer, 2014). These studies revealed the frequent use of I think in political discourse.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been made to examine the use of this type of modality in spoken and written discourse, especially political discourse (see, e.g., Baumgarten & House, 2010;Boicu, 2008;Fetzer, 2011Fetzer, , 2014Fraser, 2010;Hernández-Guerra, 2016;Lillian, 2008;López, 2012;Milkovich & Sitarica, 2017;O'Grady, 2017;Simon-Vandenbergen, 1996, 1997, 2000Vukovic, 2014ab). Some of these studies have focused on very specific features such as the form, function and distribution of the 'parenthetical' construction (Urmson, 1952) I think (Fetzer, 2011;O'Grady, 2017;Simon-Vandenbergen, 2000), and I think, I mean and I believe (Fetzer, 2014). These studies revealed the frequent use of I think in political discourse.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed the frequent use of I think in political discourse. Moreover, this parenthetical structure serves not only to express uncertainty or lack of commitment, but also to indicate tentativeness and authoritative deliberation (O'Grady, 2017;Simon-Vandenbergen, 2000). O'Grady (2017) further argues that I think is used to express either commitment to a proposition if it receives an intonational prominence or hesitation if it is followed by a filled pause.…”
Section: Introductionmentioning
confidence: 99%